INFLUENCE OF ANGIOTENSIN-CONVERTING ENZYME RAMIPRIL ON INDICATORS OF TUBULO- INTERSTITIAL RENAL DAMAGE IN PATIENTS WITH CKDI-II: GLOMERULONEPHRITIS - Dolinnayä, M.A.; Shekhovtseva, T.G. (Ukrainian Journal of Nephrology and Dialysis, 2017)
The aim: to examine the relations between morphological tubulointerstitial (TIT) parameters of kidney damage and neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) of blood serum in patients with chronic glomerulonephritis (CGN) with saved renal function, and to estimate the therapeutic correction of identified changes using ACE inhibitor ramipril.. Materials and methods. The study included 81 patients with CGN. Patients were divided into 2 clinical groups: CGN patients with arterial hypertension (AH), CGN without AH. The average daily dose of ramipril in patients with AH was 12,8 ± 5,6 mg, in patients without hypertension – 2,5 mg. We used kidney biopsy data for the analysis of renal damage on the following parameters: dystrophic and necrotic changes in tubular epithelium, thickening and/or cleavage of tubular basement membrane, presence ofcellular infiltration, interstitial fibrosis (IF). The level of NGAL and IL-18 in serum were determined by ELISA. Results. We statistically confirmed a direct link between blood NGAL and IF (r=+0,65;p<0,05), blood IL-18 and dystrophic changes in tubular epithelium (r=+0,81;p<0,05). It was established that the kidney IF diagnostic using NGAL determination in serum is highly sensitive and specific, with an efficiency of 95,3 %, and dystrophic changes in tubular epithelium via serum IL-18 – 96,6 %. Conclusion: serum levels of NGAL and IL-18 are sensitive markers of kidney TIT damage in patients with CGN with diagnostic efficiency up to 97 %. Under the influence of 24 weeks treatment with an ACE inhibitor ramipril we observed a significant decrease in levels of markers of kidney TIT damage, that confirmed nephroprotective effect of the drug.